American statesmen : secretaries of state from John Jay to Colin Powell - Mihalkanin, Edward S. (Greenwood Press, 2004)
The Secretary of State is in charge of defining and implementing U.S. foreign policy. While that role has weakened some over the past 50 years, a mere roll call of illustrious past Secretaries of State invokes the position's importance. Thomas Jefferson, Henry Kissinger, John Quincy Adams, William Jennings Bryan, Henry Clay, James Madison, George C. Marshall, George Schultz, and Daniel Webster are just a few of the Secretaries profiled within these 65 entries. Arranged A-to-Z, each essay is multifaceted, offering information personal, professional, and political. The majority of each piece dea.